ECHOCARDIOGRAPHIC INDICATORS OF THE LEFT VENTRICLЕ FUNCTIONAL CONDITIONS IN THE PERSONS OF YOUTHFUL AGE, WHO ARE ENGAGED IN PROFESSIONAL FOOTBALL - Кулієв Ф. А.,; Mehtiev, U.E.; Зейналов, А.Ф.; Ismajlova, S.S. (World of Medicine and Biology, 2013)
Object of research were football players of a male at the age from 16 till 19 years. The majority of them were members of a national team and also professional clubs. The average experience of employment by football has made 5,4 ± 2,2 years. The conducted research in football players of youthful age, has allowed to reveal presence of certain changes of a cardiac muscle. These changes carry, most likely, compensatory character connected with presence of intensive physical activities. However, on occasion already at this age a number of changes, characteristic for an initial stage of a cardiovascular pathology is registered. The given factor should become a subject of special discussion together with trainer's structure, for development of the optimal mode of training process.
Keywords: a hypertrophy left ventricular; remodeling; football